Functional observers design for descriptor systems via LMI: Continuous and discrete-time cases. (December 2017) - Darouach, Mohamed; Amato, Francesco; Alma, Marouane
Abstract: This paper investigates the design of functional observers for linear time-invariant descriptor systems. A new method for designing these observers is given by using an LMI (Linear matrix inequality) formulation. The obtained result unifies the design, it considers the continuous-time and discrete-time cases and concerns the observers of various orders.